The Role of T Follicular Helper Cells and Interleukin-21 in the Pathogenesis of Inflammatory Bowel Disease - Lulu Sun; Ruixue Kong; Hua Li; Dashan Wang (Gastroenterology Research and Practice)
T follicular helper (Tfh) cells represent a novel subset of CD4+ T cells which can provide critical help for germinal center (GC) formation and antibody production. The Tfh cells are characterized by the expression of CXC chemokine receptor 5 (CXCR5), programmed death 1 (PD-1), inducible costimulatory molecule (ICOS), B cell lymphoma 6 (BCL-6), and the secretion of interleukin-21 (IL-21). Given the important role of Tfh cells in B cell activation and high-affinity antibody production, Tfh cells are involved in the pathogenesis of many human diseases. Inflammatory bowel disease (IBD) is a group of chronic inflammatory diseases characterized by symptoms such as diarrhea, abdominal pain, and weight loss. Ulcerative colitis (UC) and Crohn’s disease (CD) are the most studied types of IBD. Dysregulated mucosal immune response plays an important role in the pathogenesis of IBD. In recent years, many studies have identified the critical role of Tfh cells and IL-21 in the pathogenic process IBD. In this paper, we will discuss the role of Tfh cells and IL-21 in IBD pathogenesis.